PENGEMASAN INFORMASI SECARA SINTAKTIS DALAM KLAUSA - * N. K. Mirahayuni (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2008)
Abstrak. This article explores constituent function differences  of syntactically design of discourses. There are two types of the designs: clause – internal and clause – external. The first type includes passive voice and dative shift. The second type comprises topicalization, left-dislocation, and cleft constructions. The design gives a speaker chances  to express lexical materials in clauses. Key words: constituent, clause, clause—internal, clause—externa